2011
DOI: 10.1016/j.ygyno.2010.12.362
|View full text |Cite
|
Sign up to set email alerts
|

A phase II, single-arm study of the anti-α5β1 integrin antibody volociximab as monotherapy in patients with platinum-resistant advanced epithelial ovarian or primary peritoneal cancer

Abstract: Objective This phase II, multicenter, single-arm, two-stage study in platinum-resistant, advanced epithelial ovarian or primary peritoneal cancer evaluated the efficacy, safety, and tolerability of weekly single-agent volociximab. Pharmacokinetic/pharmacodynamic (PK/PD) studies were also performed. Methods Sixteen patients were enrolled in Stage 1. Volociximab was administered at 15 mg/kg IV qwk until progression of disease or drug intolerability. Tumor response was assessed every 8 weeks. Serum samples for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
87
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(88 citation statements)
references
References 31 publications
1
87
0
Order By: Relevance
“…The a5b1monoclonal antibody volociximab has been in clinical trials but was abandoned in the absence of discernible clinical efficacy in a range of solid tumors, both as single agent and in combination with cytotoxic chemotherapy. [21][22][23][24] Only a few patients with prostate cancer were included in these studies and the data are insufficient to draw conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…The a5b1monoclonal antibody volociximab has been in clinical trials but was abandoned in the absence of discernible clinical efficacy in a range of solid tumors, both as single agent and in combination with cytotoxic chemotherapy. [21][22][23][24] Only a few patients with prostate cancer were included in these studies and the data are insufficient to draw conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…Phase I and II trials with Vitaxin showed some efficacy in solid cancers and metastatic melanoma (reviewed in Desgrosellier & Cheresh 2010). Volociximab was well tolerated and showed promising results in phase I trials with various solid tumours (Ricart et al 2008); however, it has shown insufficient clinical activity in ovarian cancer patients with platinum resistant disease (Bell-McGuinn et al 2011). Although promising in phase I trials, Cilengitide, an inhibitor of both αvβ3 and αvβ5 integrins, has shown limited clinical efficacy in phase II/III trials in patients with glioblastoma (Eisele et al 2014, Stupp et al 2014) and metastatic castrate-resistant prostate cancer (Bradley et al 2011).…”
Section: Role Of Fibronectin In Ovarian Cancermentioning
confidence: 99%
“…For example, multicellular aggregated formation is mediated via b1-integrins and their subsequent attachment to the mesothelium is partially dependent on a5b1-integrins (63,64). Efforts to antagonize a5b1-integrin interactions were implemented in phase II clinical trials, using a chimeric antibody, Volociximab (Table 1), in patients with platinum-resistant advanced EOC, although clinical efficacy was not accomplished (65). Moreover, targeting of a v b 3 with antibodies and radiolabeled nucleotides in xenografts has opened up new avenues and opportunities for therapeutic intervention (66)(67)(68).…”
Section: Ecm Components and Cell Adhesion Molecules Assist Cancer Migmentioning
confidence: 99%